Development of the tourist destination through organization of the VIA VINO manifestation - Fekeža, Roman (Crisis Management Days, 2024)
VIA VINO is a festival with a rich cultural, wine and gastronomic offer and is a month-long destination campaign organised in Zagreb County with the aim of promoting Zagreb’s wine roads and green ring. This destination development project was conceived, launched and implemented by the Zagreb County Tourist Board in 2021 in line with the Sustainable Tourism Development Strategy for 2030 and under the auspices of the Croatian Tourist Board and has been running for three years. The content consists of promoting and branding the wine routes of Zagreb County and creating a synergy between all stakeholders in the destination, which increases the attractive offer for visitors. The results measured over the last three years show a significant increase in the number of visitors to natural and cultural heritage sites and wine routes. At the same time, the organisation of this event has helped to increase the competitiveness of Zagreb County, increase visitor consumption, and thus increase the destination’s revenue, promote economic growth and development of the region and at the same time preserve the destination’s natural and cultural sites. The event has been held in autumn for the last three consecutive years and has had an extraordinary impact in promoting the destination and its tourism offer and resources. The paper analyses the impact of the event on the destination, preparation, branding, offer, communication tools, promotion, and the impact of the event on the development of existing and additional tourism offers, as well as the readiness and commitment of the destination’s key stakeholders, with a focus on sustainable and responsible management of tourism in the destination. It explains how the organisation and implementation of the innovative event can contribute to the multiplication of positive effects and tourism development in destinations.